How to Make Use of Facebook to Write Descriptive Texts? Bagaimana Memanfaatkan Facebook untuk Menulis Teks Deskriptif? - Irmawati, Dini Kurnia (Universitas Muhammadiyah Sidoarjo, 2019)
This study involved the junior high school students and focused on the use of Facebook through process-genre based approach to help the students solve problems related to idea development and organization in writing descriptive texts. This study used collaborative classroom action research consisting of two cycles. The findings show that the use of Facebook equipped with the descriptive scaffold through process-genre based approach could improve their skills in writing descriptive texts. The publishing on wall application also improved the student’ motivation. The scores of the students’ writing products in terms of content, organization, vocabulary, grammar and mechanics improved significantly from preliminary study to Cycle 1 and from Cycle 1 to Cycle 2. It is recommended that Facebook can be used to teach other kinds of text types and on different grades and levels of education.